The role of noise modeling in the estimation of resting-state brain effective connectivity. Issue 15 (2018) - Prando, G.; Zorzi, M.; Bertoldo, A.; Chiuso, A.
Abstract: Causal relations among neuronal populations of the brain are studied through the so-called effective connectivity (EC) network. This is estimated from EEG or fMRI measurements, by inverting a generative model of the corresponding data. It is clear that the goodness of the estimated network heavily depends on the modeling assumptions. In this present paper we consider the EC estimation problem using fMRI data in resting-state condition. Specifically, we investigate on how to model endogenous fluctuations driving the neuronal activity.